2018
DOI: 10.1016/j.celrep.2018.03.105
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Model Using Human Cerebral Organoids

Abstract: We have developed a cancer model of gliomas in human cerebral organoids that allows direct observation of tumor initiation as well as continuous microscopic observations. We used CRISPR/Cas9 technology to target an HRas-IRES-tdTomato construct by homologous recombination into the TP53 locus. Results show that transformed cells rapidly become invasive and destroy surrounding organoid structures, overwhelming the entire organoid. Tumor cells in the organoids can be orthotopically xenografted into immunodeficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
334
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(343 citation statements)
references
References 20 publications
5
334
1
3
Order By: Relevance
“…Previous in vitro models have suffered from limited physiological relevance or have been incompatible with the time scales for clinical decision-making 6 . Recent studies have shown that human cerebral organoids can be used as a platform for tumor cell transplantation or genetic engineering of tumors, enabling microscopic observation of tumor development [13][14][15] . However, tumor cell interactions with normal brain cells have not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro models have suffered from limited physiological relevance or have been incompatible with the time scales for clinical decision-making 6 . Recent studies have shown that human cerebral organoids can be used as a platform for tumor cell transplantation or genetic engineering of tumors, enabling microscopic observation of tumor development [13][14][15] . However, tumor cell interactions with normal brain cells have not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, PDX models are restricted by variable engraftment efficiency, mixing with animal cells, limited throughput, and long latency in tumor generation, which limits their usefulness for testing personalized therapies 27 . Cerebral organoids, self-organizing 3D cultures that resemble the developing brain 28 , have been genetically altered to develop oncogenic properties or co-cultured with tumor spheres to model tumor cell invasion 29,30 . While cerebral organoids are useful, readily manipulatable models, they represent only the fetal brain without important non-neural cell types, such as immune and endothelial cells, and do not recapitulate the cellular diversity or architecture of glioblastoma tumors.…”
Section: Development Of Glioblastoma Organoid Culture and Biobankingmentioning
confidence: 99%
“…While this study already proves the potential of brain organoids to help understand tumorigenesis, variations in expression levels of oncogenes from organoid to organoid requires further refinement of the methodology. Ogawa et al devised an elegant method to study the invasion behavior of patient‐derived glioblastoma cell lines in brain organoids and identified that GBM cells have the ability to invade within the 3D neuroepithelium. This method basically establishes human brain organoids as a platform to further characterize the invasive behavior of patient‐derived GBM cells.…”
Section: Expectations From the Current State‐of‐the‐art Organoidsmentioning
confidence: 99%